2014
DOI: 10.1007/s00270-014-0888-z
|View full text |Cite
|
Sign up to set email alerts
|

Intranodal Lymphangiogram: Technical Aspects and Findings

Abstract: INL succeeded in all patients. Lipiodol leaked into the vein through a lymphaticovenous anastomosis at the femoral or pelvic region in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 8 publications
2
37
0
1
Order By: Relevance
“…Lipiodol (Terumo, Tokyo, Japan) injection was performed manually at a rate of 0.1 mL/min. During the injection, fluoroscopy was used intermittently to confirm that the injected lipiodol was entering the lymphatic vessels [9].…”
Section: Discussionmentioning
confidence: 99%
“…Lipiodol (Terumo, Tokyo, Japan) injection was performed manually at a rate of 0.1 mL/min. During the injection, fluoroscopy was used intermittently to confirm that the injected lipiodol was entering the lymphatic vessels [9].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that the junction of the hilum and cortex should be targeted to achieve success. 28,29 Although this is also true in our experience, lymphangiography was nevertheless successful in any location regardless of whether the cortex or hilum was punctured. However, because of abundant fat within the hilum, a higher rate of extravasation was demonstrated when the needle tip was positioned at the center of the lymph node.…”
Section: Equipment and Techniquementioning
confidence: 63%
“…Lipiodol injection was performed manually using a 3-mL syringe and controlled injection was performed allowing 3 mL of Lipiodol to be injected over a time of 6 minutes (0.5 mL/min). This rate is a little faster than that described in an earlier study by Kariya et al 28 where the injection rate was either 1 mL/3 min. The rate ranges between 0.2 and 0.4 mL/min in other reports.…”
Section: Equipment and Techniquementioning
confidence: 67%
See 2 more Smart Citations